Cosmologies, Heritagization and Eco-symbols in the Catalan Pyrinees within a Global Perspective - Frigolé Reixach, Joan (Revista de Antropología Social, 2012)
The paper analyses the relationship between diverse cosmologies, the heritagization of culture and nature and the eco-symbols in a former peasant territory reshaped by the collapse of peasant economy, the depopulation and the development of a service economy. The creation of a natural park, the progressive landscape’s wilderness and the presence of new categories of people set the conditions for the coexistence of different perceptions and practices relative to nature. The paper distinguishes three cosmologies with different conceptions of nature and their relationship with society. Both the heritagization of nature and the cosmology based on the notion of biodiversity generate eco-symbols that have a great importance for enterprises as they add value to its logos and brands in a global market. This is one of the three global references that contextualize local ethnography.